Normal Development of Voice - Pedersen, Mette (Springer International Publishing : Imprint: Springer, 2024)
This fully revised and extended second edition provides a comprehensive, most up-to-date overview of the investigation of quantitative measurement in the complex of voice. Important objective parameters of normal voice development are assessed, especially relevant when pathological deviations have to be recognized and defined. The description of different qualities of normal voice development in terms of measurable parameters is provided. The book highlights the hormonal changes that have a considerable influence on the physical development of boys and girls, and how it is possible to predict the voice transition statistically. The extent to which hormones affect voice development in the two genders are made clear in this work through the observation of a number of parameters. In this second edition, the focus is extended to include High-Speed Video images and further discussion. Possible interesting topics for further research are also emphasized. This book will be a valuable resource for laryngologists, phoniatricians, and teachers in their daily work. This is an open access book.